Job Satisfaction as The Key Connector Between Leadership and Employee Performance - Arief, Mohammad Hasan; Mulyono, Djoko Tri; Oktaviana, Helma Nurra; Suyono, Joko; Elisabeth, Damarsari Ratnasahara (INNOVATION RESEARCH JOURNAL, 2025)
This research was conducted at the Administratie Village of Pacarkembang and Kapas Madya Baru, Surabaya, Indonesia. The aim was to analyze the influence of leadership on employee performance, with job satisfaction as a mediating variable. The population in this study was 35 employees of the Administratie Village of Pacarkembang and Kapas Madya Baru, Surabaya, Indonesia. The sampling technique used total sampling. Data analysis used Structural Equation Modeling (SEM) with Partial Least Squares (PLS). The results showed that leadership influences employee performance and job satisfaction, job satisfaction influences employee performance, and leadership influences employee performance through employee performance